2013
DOI: 10.11114/ijsss.v1i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Assessment and Portfolios: Review, Reconsider, and Revitalize

Abstract: The concept of evaluating performance in relation to an established objective is certainly not a new idea. The use and application of alternative assessments is likewise not a revolutionary notion. However, the mechanics and potential applications of the portfolio as one area of alternative assessment do deserve reconsideration with the purpose of a renaissance of this valuable and self-motivating type of formative and summative evaluation. The application of the portfolio to student, teacher, employment, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…A battery of studies was carried out to explore one alternative assessment format and its impact on one or several dependent variables. For instance, Sandford and Hsu (2013) found that alternative assessments and especially portfolios deserve reconsideration because of their invaluable and motivating role in both formative and summative evaluation. In the same perspective, Gozuyesil and Tanriseven (2017) also demonstrated that portfolios as an alternative assessment technique have a substantial impact on students' academic achievement revealed especially in mathematics courses.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…A battery of studies was carried out to explore one alternative assessment format and its impact on one or several dependent variables. For instance, Sandford and Hsu (2013) found that alternative assessments and especially portfolios deserve reconsideration because of their invaluable and motivating role in both formative and summative evaluation. In the same perspective, Gozuyesil and Tanriseven (2017) also demonstrated that portfolios as an alternative assessment technique have a substantial impact on students' academic achievement revealed especially in mathematics courses.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…Bu araştırmada Fen Bilimlerinin Besinlerin Sindirimi konusunun öğretim uygulamasındaki doğrudan öğretim yöntemine ek olarak öğretim sürecinin başında,ortasında ve sonunda kullanılan alternatif değerlendirme tekniğinin yukarıda sıralanan avantajlardan dolayı etkili olduğu düşünülmektedir. Normal gelişim düzeyindeki öğrencilerin belli bir konuya yönelik performansının yanı sıra öğrenme-öğretme sürecini etkileyen değişkenlerin çok yönlü bir şekilde değerlendirilmesini sağlayan alternatif değerlendirme tekniklerinin (Sandford ve Hsu, 2013), bu araştırmada yer alan ZY olan özel gereksinimli öğrencinin hem performansının hem de sürecin değerlendirilmesinde etkili olduğu görülmektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…Alanyazında, özel eğitimde alternatif değerlendirme tekniklerinin kullanıldığı yurt dışında gerçekleştirilmiş araştırmalar bulunamamış ancak genel eğitimde alternatif değerlendirme tekniklerinin kullanıldığı araştırmalara rastlanmıştır (Sandford ve Hsu, 2013;Zimbicki, 2007). Örneğin Zimbicki (2007) tarafından gerçekleştirilen bir nitel eylem araştırmasında, normal gelişim düzeyindeki öğrenciler üzerinde alternatif değerlendirme tekniklerinin, öğrencilerin motivasyon ve öz yeterlilik düzeyleri üzerindeki etkisinin incelenmesi amaçlanmış ve sözlü sınav, performans değerlendirme, işbirliğiyle öğrenme, ürün değerlendirmesi, uygulamalı dersler ve portfolyoların oluşturulmasını içeren çeşitli değerlendirme tekniklerine yer verilmiştir.…”
Section: Introductionunclassified
“…Besides, very few research focused on students' attitudes towards portfolio assessment, in particular in ESP classes (Hamp-Lam 2013 cited in Burner, 2014). Nevetheless, according to Sandford & Hsu (2013), portfolio can contextualize learning and facilitate students' involvement in the learning process.…”
Section: Introductionmentioning
confidence: 99%